AN IRON-RICH PRODUCT FROM SCALE - T. N. Lipatkina (Литьë и металлургия)
Possibility of solid-phase restoration of ferriferous scale by various reducing agents is studied in the article. Tests on solidphase restoration of scale by a firm reducers in the developed laboratory rotary installation are carried out. As a result of tests the iron-rich product with the general content of iron of 87% is received, degree of metallization 96,2%.